Efficient hardware architectures of Lilliput lightweight algorithm for image encryption. (5th October 2022) - Singh, Pulkit; Patro, K. Abhimanyu Kumar; Acharya, Bibhudendra; Chaurasiya, Rahul Kumar
With the advancement of communication networks, information security has become extremely crucial in storage and transmission. As images are used in most of the networks, hence image security is becoming a challenging task. This paper proposes two hardware architectures of Lilliput lightweight block cipher. These hardware architectures are implemented on FPGA and ASIC platforms compared with state-of-the-art designs. In these architectures, first, 8-bit and then 16-bit serial structures are designed to implement. The serialised designs of 8-bit and 16-bit imply low area by consuming less number of slices. Finally, these serialised architectures are utilised for image encryption with the help of a controller. The simulation results and security analysis for hardware generated encrypted images show the better performance of proposed architectures and stronger resistance against entropy attack, differential attack, and statistical attacks.